Shiga toxin-producing Escherichia coli O157, O26 and O111 in cattle faeces and hides in Italy - Bonardi, S. (Vet Rec Open, 2015)
INTRODUCTION: Ruminants are regarded as the natural reservoir for Shiga toxin-producing Escherichia coli (STEC), especially of serogroup O157. MATERIALS AND METHODS: During 2011 and 2012, 320 samples (160 faecal samples from the rectum and 160 hide samples from the brisket area) were collected from 160 cattle at slaughter in Northern Italy during warm months (May to October). Cattle were reared in different farms and their age at slaughter ranged between nine months and 15 years, most of them being culled cattle (median age: six years; average age: 4.6 years). Samples were tested by immunomagnetic-separation technique for E coli O157 and O26 and by a screening PCR for stx genes followed by cultural detection of STEC. The virulence genes stx1, stx2, eae, and e-hlyA were detected and among stx2-positive isolates the presence of the stx2a and stx2c variants was investigated. RESULTS: Twenty-one of 160 cattle (13.1 per cent; 95 per cent CI 8.3 to 19.4 per cent) were found to be faecal carriers of STEC. STEC O157 was found in 10 (6.3 per cent) samples, STEC O26 in six (3.8 per cent) and STEC O111 in one (0.6 per cent). Four isolates (2.5 per cent) were O not determined (OND). Six out of 160 (3.8 per cent; 95 per cent CI 1.4 to 8.0 per cent) hide samples were positive for STEC; four hides (2.5 per cent) were contaminated by STEC O157 and two (1.3 per cent) by STEC O26. In three cattle (1.9 per cent) STEC from both faeces and hides were detected. Among STEC O157, 87.5 per cent of them carried the stx2c gene and 12.5 per cent carried both stx1 and stx2c genes. No O157 isolate harboured stx2a variant. STEC O26 and O111 carried the stx1 gene only. One OND strain carried both the stx2a and stx2c genes. CONCLUSIONS: This study shows that STEC O157 from cattle can harbour the stx2c variant, which is associated with haemolytic uraemic syndrome in humans, and that cattle hides may be a source of human pathogenic STEC O157 and O26 in the slaughterhouse environment.